Straight to the Point: How people encode linear discontinuations (Fractal: Revista de Psicologia, 2012)
Spatial discontinuations occuring in cities introduce ambiguity in people´s mental spatial encoding and wayfinding bahavior. How do we encode and classify such misalignments? Twenty participants were asked to classify a total of 51 icons showing an upward-moving line being misaligned to the right and left as well as starting straight. The results show that subjects were very sensitive to slight discontinuations occurring to the vertical lines and that there was not exact symmetry between the left and right axis, meaning that the pieces slightly misaligned to the left were encoded differently than those misaligned to the right.